Pengaruh Komunitas Fandom Dan Perilaku Konsumtif Terhadap Keputusan Pembelian Irasional Dengan Minat Beli Dan Kesediaan Membayar Sebagai Variabel Intervening: Studi Kasus: Pembelian Album dan Merch Penggemar Grup Exo di Twitter - Puspita Zahra, Mayang; Chasanah, Uswatun (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
This study aims to analyse the effect that influence the irrational buying decision of album and merchandise Exo group by fans on Twitter 2022. The research is testing by directly are fandom and consumptive behaviour on irrational buying decision, and through intervening variables are irrational buying interest as mediation and willingness to pay as moderation. The population of this research is followers of @aeribase account twitter which is the fan base of Indonesian Exo group fans. By using purposive sampling technique, obtained 100 accounts twitter as research samples. Based on the result of study, there are effect of consumptive behaviour directly or through by irrational buying interest on irrational buying decision. Other variable is fandom has effect indirectly by irrational buying interest on irrational buying decision. The research also proves that there is a moderation effect of willingness to pay from irrational buying interest on irrational buying decisions.